Motion of the dayside polar cap boundary during substorm cycles: I. Observations of pulses in the magnetopause reconnection rate - Lockwood, M.; Moen, J.; van Eyken, A. P.; Davies, J. A.; Oksavik, K.; Mccrea, I. W. (HAL CCSD, 2005)
International audience Using data from the EISCAT (European Incoherent Scatter) VHF radar and DMSP (Defense Meteorological Satellite Program) spacecraft passes, we study the motion of the dayside open-closed field line boundary during two substorm cycles. The satellite data show that the motions of ion and electron temperature boundaries in EISCAT data, as reported by Moen et al. (2004), are not localised around the radar; rather, they reflect motions of the open-closed field line boundary at all MLT throughout the dayside auroral ionosphere. The boundary is shown to erode equatorward when the IMF points southward, consistent with the effect of magnetopause reconnection. During the substorm expansion and recovery phases, the dayside boundary returns poleward, whether the IMF points northward or southward. However, the poleward retreat was much faster during the substorm for which the IMF had returned to northward than for the substorm for which the IMF remained southward - even though the former substorm is much the weaker of the two. These poleward retreats are consistent with the destruction of open flux at the tail current sheet. Application of a new analysis of the peak ion energies at the equatorward edge of the cleft/cusp/mantle dispersion seen by the DMSP satellites identifies the dayside reconnection merging gap to extend in MLT from about 9.5 to 15.5 h for most of the interval. Analysis of the boundary motion, and of the convection velocities seen near the boundary by EISCAT, allows calculation of the reconnection rate (mapped down to the ionosphere) from the flow component normal to the boundary in its own rest frame. This reconnection rate is not, in general, significantly different from zero before 06:45 UT (MLT<9.5 h) - indicating that the X line footprint expands over the EISCAT field-of-view to earlier MLT only occasionally and briefly. Between 06:45 UT and 12:45 UT (9.5